ANALISIS BIAYA OPERASIONAL DAN PENDAPATAN OPERASIONAL TERHADAP RETURN ON ASSETS PADA PT BANK TABUNGAN NEGARA (PERSERO) TBK - Sofyan Marwansyah (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2015)
Earnings or profitability of the business and is used to measure the level of business efficiency and profitability achieved by bank.Untuk maintain a decent level of profitability, the bank must earn to cover the costs and the bank must strive constantly maintain a certain level of income by taking into account risk factors dihadapi.metode research used in the preparation of this thesis is the observation method is to do a street vendor in the State Savings Bank (Persero) Tbk, study the documentation that is by collecting several topics related to the study of books, internet sites, as well as collect data annual basis through the period 2003-2013 financial statements of the bank in the form of balance sheet and profit / loss have been published and simple linear regression analysis method through IBM SPSS Statistics software 21.Tujuan of this research was to determine the relationship, influence, and the regression equation formed from Operating Expenses and Operating Income (ROA) on Return On Assets (ROA) .From the results of analysis showed that the ROA has a weak relationship and not the direction of the ROA amounted to -0.039, and ROA have a significant effect on ROA of 47.7% while the remaining 52.3% is influenced by other factors. The regression equation that can be formed is y = 4,793-0,039x. Keywords: Operating Costs and Operating Income (BOPO), Return on Assets (ROA)